High-resolution ultrasound of peripheral neuropathies in rheumatological patients: An overview of clinical applications and imaging findings - Zaottini, Federico; Picasso, Riccardo; Pistoia, Federico; Sanguinetti, Sara; Pansecchi, Michelle; Tovt, Luca; Viglino, Umberto; Cabona, Corrado; Garnero, Martina; Benedetti, Luana; Martinoli, Carlo (Frontiers in Medicine, 2022)
Peripheral neuropathies are surprisingly common and can be associated with a number of conditions, including rheumatological diseases. Whether the co-existence of peripheral neuropathies with rheumatological disorders is coincidental or related to a common pathogenic mechanism, these disabling conditions can affect the outcome of rheumatological patients and should be targeted with specific treatment. The clinical presentation of peripheral neuropathy can be multifaceted and difficult to recognize in polysymptomatic patients. However, physicians adopting state-of-art diagnostic strategies, including nerve imaging, may improve the detection rate and management of neuropathies. In particular, a diagnostic approach relying exclusively on clinical history and nerve conduction studies may not be sufficient to disclose the etiology of the nerve damage and its anatomical location and thus requires integration with morphological studies. High-Resolution Ultrasound (HRUS) is increasingly adopted to support the diagnosis and follow-up of both joint disorders in rheumatology and peripheral neuropathies of different etiologies. In this review, the different types of nerve disorders associated with the most common syndromes of rheumatological interest are discussed, focusing on the distinctive sonographic features.